The Microbial Regulation of Global Biogeochemical Cycles - Johannes Rousk (Frontiers Research Topics, 2014)
Global biogeochemical cycles of carbon and nutrients are increasingly affected by human activities. So far, modeling has been central for our understanding of how this will affect ecosystem functioning and the biogeochemical cycling of carbon and nutrients. These models have been forced to adopt a reductive approach built on the flow of carbon and nutrients between pools that are difficult or even impossible to verify with empirical evidence. Furthermore, while some of these models include the response in physiology, ecology and biogeography of primary producers to environmental change, the microbial part of the ecosystem is generally poorly represented or lacking altogether. The principal pool of carbon and nutrients in soil is the organic matter. The turnover of this reservoir is governed by microorganisms that act as catalytic converters of environmental conditions into biogeochemical cycling of carbon and nutrients. The dependency of this conversion activity on individual environmental conditions such as pH, moisture and temperature has been frequently studied. On the contrary, only rarely have the microorganisms involved in carrying out the processes been identified, and one of the biggest challenges for advancing our understanding of biogeochemical processes is to identify the microorganisms carrying out a specific set of metabolic processes and how they partition their carbon and nutrient use. We also need to identify the factors governing these activities and if they result in feedback mechanisms that alter the growth, activity and interaction between primary producers and microorganisms. By determining how different groups of microorganisms respond to individual environmental conditions by allocating carbon and nutrients to production of biomass, CO2 and other products, a mechanistic as well as quantitative understanding of formation and decomposition of organic matter, and the production and consumption of greenhouse gases, can be achieved. In this Research Topic, supported by the Swedish research councils' programme "Biodiversity and Ecosystem Services in a Changing Landscape" (BECC), we intend to promote this alternative framework to address how cycling of carbon and nutrients will be altered in a changing environment from the first-principle mechanisms that drive them - namely the ecology, physiology and biogeography of microorganisms - and on up to emerging global biogeochemical patterns. This novel and unconventional approach has the potential to generate fresh insights that can open up new horizons and stimulate rapid conceptual development in our basic understanding of the regulating factors for global biogeochemical cycles. The vision for the research topic is to facilitate such progress by bringing together leading scientists as proponents of several disciplines. By bridging Microbial Ecology and Biogeochemistry, connecting microbial activities at the micro-scale to carbon fluxes at the ecosystem-scale, and linking above- and belowground ecosystem functioning, we can leap forward from the current understanding of the global biogeochemical cycles.